Management Practices and Mergers and Acquisitions - Bai, John (Jianqiu); Jin, Wang; Serfling, Matthew (Management Science, 2022)
Using a novel data set of establishment-level management practices from the U.S. Census Bureau, we show that firms with more specific, formal, frequent, or explicit (i.e., “structured”) management practices tend to acquire establishments with less structured management practices and, following the acquisition, adopt more structured practices at the target establishments. These changes are larger when acquirers have a greater incentive and ability to make changes and are also associated with improvements in establishment performance. Overall, our findings suggest that the adoption of more structured management practices constitutes an important source of value creation in mergers and acquisitions. This paper was accepted by Tomasz Piskorski, finance.